New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus - Cornel, Anthony John; Mayi, Marie Paul Audrey; Kowo, Cyril; Foncha, David; Andongma, Esack; Anong, Damian Nota; Elad, Mirabel; Djomo, Charlene; Tchuinkam, Timoleon; Brisco, Katherine K.; Sehgal, Ravinder (Zootaxa, 2020)
Species of Culex (Diptera: Culicidae) belonging to the subgenus Culiciomyia were collected in partially logged areas and in surrounding pristine forest (Talangaye Forest) in the Nguti Subdivision in the South-West Region of Cameroon. Mosquitoes were collected mainly by sweep netting through forest floor vegetation. Morphological species identification of African Culiciomyia relies almost exclusively on the structure of the male genitalia and the shapes of comb scales on the maxillary palpi of males. Other features of males and the habitus of females are largely indistinguishable between the species of this subgenus. In total, seven currently described species and three new species were collected in the forest. The males of the three new species are described and named as Culex apicopilosus Cornel & Mayi, sp. n., Culex lanzaroi Cornel & Mayi, sp. n. and Culex pseudosubaequalis Cornel & Mayi, sp. n. More detailed descriptions of males of the other currently known species that were collected in the Talangaye Forest and pictorial keys to the males of all Afrotropical species of Culiciomyia, including the new species, are provided.